Historical thinking skills available to primary school teachers (Journal of the College of Basic Education, 2023)
The teacher in Iraq, especially the history teacher, faces many widespread objections and criticisms from most supervisors, educators, specialists, and parents of students. (2004) and (Al-Bahadli et al., 2009) and (Al-Halfi, 2011), to their inability to link relationships, draw generalizations, elicit ideas correctly, and realize and understand the ideas that are put forward by learners or how to benefit from this information in solving other problems in the future, This, in turn, affects their intellectual development.This educational problem is not considered special in our schools only, as it is almost a global problem in many schools in the world, even if it varies in size and depth (88 Yeager & Wilson, 1997), so some societies intensified efforts and harnessed the capabilities and prepared programs that help him learn the skills of thinking of all kinds, and on The necessity of not looking at history as a mass of facts, dates, forms and symbols, but rather trying to explain the development that occurred in the lives of different nations and civilized societies and how and why did this development occur? By showing the interdependence between these events (Barqi, 2008: 146).